Optimalisasi Organizational Citizenship Behavior (OCB) Pada Pegawai Dinas Di Kabupaten Lumajang - Sukma Irdiana; Kusnanto Darmawan (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
This study aims to determine the effect of job satisfaction, organizational commitment and organizational culture partially and simultaneously to organizational citizenship behavior (OCB) on official staff in Lumajang District. The research type used is descriptive with causal associative approach. This study was conducted with the number of respondents as many as 147 people. The sampling technique used is a saturated sampling technique. Hypothesis testing is done by multiple linear regression analysis for hypothesis through SPSS 16 for windows program. Based on the results of the study obtained that the satisfaction of employees and organizational culture there is a significant positive influence partially on organizational citizenship behavior (OCB) on the official staff in Lumajang District. While organizational commitment there is no significant positive effect partially on organizational citizenship behavior (OCB) on official employees in Lumajang District. Simultaneously employee satisfaction, organizational commitment and organizational culture there is a significant positive influence simultaneously to organizational citizenship behavior (OCB) on official staff in Lumajang District. The variables studied have an effect of 63.3% on the organizational citizenship behavior (OCB) and the rest is influenced by other variables that are not in carefully.